2017
DOI: 10.5812/archcid.62005
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma Gondii Infection and Related Risk Factors Among Blood Donors in Northwest Iran

Abstract: Background: Toxoplasmosis, a worldwide parasitic infection, is considered as a transfusion-transmitted disease. Objectives: Due to ignorance about Toxoplasma infection in blood donors monitoring and its important role in provision of safe blood and blood products and also poor information about the seroprevalence of T. gondii infection in blood donors, this study was conducted to assess anti-Toxoplasma gondii antibodies and associated risk factors among blood donors in northwest of Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Similarly, a study in Kirkuk by Obaid et al (13) also reported higher rates of total and chronic seroprevalence of toxoplasmosis about (18.6% and 11.6%), and a lower rate (4.6%) for acute toxoplasmosis. A study by Bahhaj R et al (14) also reported a high seropositive rate for IgG (39.36%) and a low seropositive rate for IgM (1.06%) among healthy blood donors.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, a study in Kirkuk by Obaid et al (13) also reported higher rates of total and chronic seroprevalence of toxoplasmosis about (18.6% and 11.6%), and a lower rate (4.6%) for acute toxoplasmosis. A study by Bahhaj R et al (14) also reported a high seropositive rate for IgG (39.36%) and a low seropositive rate for IgM (1.06%) among healthy blood donors.…”
Section: Discussionmentioning
confidence: 92%
“…Many studies suggest enhancing blood safety measures of pregnant, immunocompromised, and multi-transfused patients. For this purpose, the screening for T. gondii as a priority test for all pretransfusion blood testing schedules should be performed (especially in regions with high endemicity) [ 26 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, ToxoDB genotype #13 from the Caribbean had a level of virulence similar to that of ToxoDB genotype #6 from Brazil in killing infected mice within 8 days (Hamilton et al, 2019). The link between different T. gondii molecules, including ROPs (Kappe et al, 2004;Schwartz, 2013;McFarland et al, 2016) and dense granules (Bahhaj et al, 2017), is less recognized. However, a Chinese study indicated a linkage between these molecules to strain virulence, demonstrated as a reduced immune response by mice to the parasite and variation in some key genes among the same genotypes of the parasite (Cheng et al, 2017).…”
Section: Toxoplasma Genotypes and Virulencementioning
confidence: 99%
“…Patients with acute infection may develop cervical lymphadenopathy and influenza-like illness. Rarely, an organ transplant or blood donation recipient is infected by T. gondii when they receive an organ or blood from a T. gondii-positive donor (Patel and Paya, 1997;Morris et al, 2010;Schwartz, 2013;Bahhaj et al, 2017;White et al, 2018). In immunocompromised patients and during trans-placental infection, toxoplasmosis most frequently causes neurological complications or toxoplasmic encephalitis (McFarland et al, 2016).…”
Section: Introductionmentioning
confidence: 99%